Nutritional management for patient with CKD stage 4 secondary to diabetic nephropathy with underlying type 2 diabetes mellitus and hypertension - Ying, C.Y. (2021)
Assessment Mr. TM is a 78 years old Malay male diagnosed with CKD stage 4 secondary to diabetic nephropathy since 2019. The patient has underlying type 2 diabetes mellitus, hypertension, cholestasis, increased liver echogenicity, bilateral renal parenchymal diseases with multiple renal cysts, prostatomegaly, and hypercholesterolemia. He is a pensioner and stays with his daughter. His siblings have a history of DM and hypertension. He currently using a walking stick. His weight is 69.8kg and his height is 156 cm. Patient BMI is 28.7kg/m2 which is considered normal according to Queensland, 2013. His renal profile shows a high reading for urea, potassium, and creatinine. In addition, his GFR reading is at 17 which indicates that the patient has CKD stage 4. His lipid profile shows normal readings except for HDL which slightly lower than the normal average. For glucose profile, his HbA1C reading is at 6.6% which is slightly higher than normal. Mr. TM's clinical data shows normal reading for blood pressure and pulse rate but he has a poor urine output. His dietary assessment shows an energy intake of about 1279kca1/day and his protein intake is 41g/day. Diagnosis The patient's nutritional diagnosis is inadequate protein-energy intake (NI-5.2) related to food and nutrition-related knowledge deficit concerning the appropriate amount of energy and protein as evidence by protein intake is 41g/day @ 73% from protein requirement and energy intake is 1279 kcal/day @ 73% from energy requirement. Intervention The main goal is to slow down the progression of kidney failure by educating the patient about a pre-dialysis diet that involving limiting protein and potassium intake. The second goal is to ensure that the blood sugar profile is maintained within normal range by reemphasizing a diabetic diet. Monitoring & Evaluation For the next follow-up, the patient's weight changes, renal profile, and HbA1 C are required for monitoring.